Water quality assessment in the pitimbu River Basin in Rio grande do Norte - Lima, Wédina Rodrigues de; Rocha, Reynaldo Melo Cavalcante; Gosson, Priscila Cavalcante da Rocha; Santos, Nelson Césio Fernandes do; Sena, Shirley Feitosa Machado (Revista Hipótese, 2017)
This study evaluates the quality of water in the River Basin Pitimbu, through the analysis of the Water Quality Index (WQI) and Trophic State Index (TSI) in the period 2014 to 2015 in six collection points. Two points had the WQI lower than the others and has the TSI introduced herself between oligotrophic and mesotrophic, considering low productivity and intermediate nutrient. Thus, we emphasize the importance of systematic monitoring to prevent the water body.